Analysis of Language Errors for Level 3 BIPA Learners at the University of Social Sciences and Humanities, Hanoi - Asrianti Asrianti (Budapest International Research and Critics University, 2022)
Language errors in language learning also occur in BIPA students (Indonesian for foreign speakers). The mistakes made are mostly because the structure of the language being studied is different from the language of origin of the learner's country. Analysis of language errors is an effort made to correct language errors made by BIPA students to find out the factors that cause errors made by students, correct errors and prevent language errors from occurring. Descriptive qualitative research method. The data sourced from the research are BIPA level 3 students at the University of Social Sciences and Humanities (USSH) in 2022 totaling 21 students while the research data is written language errors in the recount text of BIPA students. Data collection techniques in the form of assignment techniques, reading and note-taking techniques. Furthermore, the data analysis techniques are (1) Identifying errors, (2) Classifying errors, 3) Describing the level of errors, and (4) Evaluating errors. The results of the study showed data on language errors, namely (1) syntax level errors as much as 32%, (2) semantic level errors 26%, (3) morphological level errors 22% and spelling level errors 16%.